Factors influencing the intention to use buy now pay later in Malaysia - Loh, Pui Yee (2023)
Buy Now Pay Later (BNPL) has become more and more famous in the last few years, especially during the Covid-19. People all around the world started to use Buy Now Pay Later when they were purchasing online via certain applications such as Atome, SpayLater, Hoolah, so on and so forth. Thus, the aim of this research is to study the relationship between performance expectancy, effort expectancy, facilitating conditions, social influence, materialism, trust, and satisfaction with the intention to use Buy Now Pay Later in Malaysia. In this study, the researcher has adopted the Unified Theory of Technology Acceptance and Technology Use (UTAUT) to develop a conceptual framework based on the context of Buy Now Pay Later.